Perbandingan Hasil Belajar Matematika Melalui Pembelajaran Kooperatif Tipe Number Head Together dan Student Team Achievement Division Pada Siswa MTs Muhammadiyah Penyasawan Kecamatan Kampar - Desi Anggraini (Instructional Development Journal, 2018)
This article aims to determine the differences in the results of learning mathematics by using the appropriate learning model in the application of cooperative learning model Number Head Type Togeteher (NHT) and Student Team Achievement Division (STAD) on the subject of Circles at MTs Muhammadiyah Penyasawan, Kampar District. In this research the problem statement is "Are there differences in learning outcomes of mathematics using Cooperative learning models Number Head Together (NHT) and Student Achievement Division (STAD) types in class VIII MTs Muhammadiyah Penyasawan Kampar District on the subject of Circles?" This article uses comparative research which found a difference between the use of Cooperative learning models Number Head Together (NHT) and Student Achievement Division (STAD) types, in this study the researchers played a direct role as teachers in the learning process. In this study Cooperative Learning NHT type is X1 and STAD type is X2 variable and learning result is Y variable. The population of this study is all Muhammadiyah MTS students and the sample used is VIIIA class as a class using Cooperative Learning Type Number Head Together (NHT) and class VIIIB as a class that uses Student Team Achievement Divison (STAD) Type Learning Model. The research subjects were eighth grade eighth grade students and the object was learning outcomes using the cooperative learning type NHT model and learning outcomes using the STAD learning model. The data collection technique is in the form of observation, documentation and tests conducted at the sixth meeting after the learning meeting is complete. This data is processed using the test-t formula and obtained a t value of 4.115 with a significant value of 2.69 where the significant value obtained from the calculation is greater than the significance level α = 0.05, then Ha is accepted. Based on the results of the data analysis, it was concluded that there were differences in the mathematics learning outcomes of students using the Cooperative learning model Number Head Together (NHT) and Student Achievement Division (STAD) types on the subject of the Circle at MTs Muhammadiyah Penyasawan Kampar Distric